Transitions to Adulthood for Children with Special Health Care Needs - McDonald, Kate (The University of Arizona., 2011)
Background: Every year in the United States approximately half a million youth with special health care needs (SHCN) turn 18. Little is known about how this population fares during the transition to adulthood. Purpose: To examine transitions to adulthood for young adults with SHCN. Methods: Using data from two national longitudinal surveys: the Panel Study of Income Dynamics and the Survey of Adult Transitions and Health, I built linear and logistic regression models to evaluate the relationship between having a history of SHCN during childhood and key transitional outcomes during young adulthood (e.g., mental health status, educational attainment, employment, financial independence and subjective indicators of adulthood). A second set of logistic models examined associations between hypothesized risk and protective factors during childhood (e.g. family financial burden, care in a medical home and access to adequate insurance) and physical health outcomes during young adulthood for youth with SHCN. Multivariate models were adjusted for key confounders. Results: The majority of youth with a history of SHCN were doing well during the transition to adulthood. That said, compared to young adults without a history of SHCN, young adults with a history of SHCN were in significantly worse mental health (adjusted OR of experiencing a non-specific psychological disorder 3.90, 95% CI 1.78-8.53) and had significantly lower odds of graduating from high school (adjusted OR 0.55, 95% CI 0.32-0.96), attending college (adjusted OR 0.61, 95% CI 0.38-0.96), and receiving financial assistance from their families (adjusted OR 0.56, 95% CI 0.38-0.83). Amongst young adults with a history of SHCN, family financial burden during childhood significantly decreased the odds of being in good physical health during the transition to adulthood. There was limited evidence that receipt of care in a medical home or access to adequate insurance during childhood increased the odds of being in good physical health for young adults with a history of SHCN. Conclusions: These findings have important policy implications for programs serving youth with SHCN. Specifically, mental health and educational services may need to be expanded and more emphasis placed on addressing the non-medical determinants of health, like family financial burden.